Kształtowanie się statusu prawnego Morza Kaspijskiego - Łyszczak, Paweł (The Formation of the Caspian Sea Legal Status, 2008)
Legal status of the Caspian Sea has been an issue for riparian states since 1991. Oil and gas discoveries changed the problem of legal definition of this body of water to a geopolitical one. Division of the hydrocarbons has become the main subject of discussion. Russian Federation and Iran, which have relatively small reserves of energy resources in their parts of the Caspian Sea, were more interested in common use of the sea resources. Whereas countries rich in oil and gas, e.g. Azerbaijan, were aiming to divide Caspian among riparian states. So far no final solution has been applied. However, riparian states are using bilateral agreements, which in the future might become a base for an agreement among all states. Most probably natural resources of the Caspian will be divided, but the water surface will remain common for all riparian states.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 147-157